The Black British Racial Trauma Questionnaire (BBRTQ): A Culturally Grounded Framework for Assessing Racial Trauma Among Black People in the UK - Delroy Constantine-Simms (My University, 2025)
Racial trauma remains under-assessed in UK mental health practice, particularly among Black British individuals facing systemic, interpersonal, and historical racism. Standard diagnostic tools—such as the PCL-5, DASS-21, and ACE Questionnaire—fail to recognise racism as a distinct trauma source. U.S.-centric instruments like the RBTSSS and UnRESTS offer targeted assessments but lack cultural relevance in British contexts. This study introduces the Black British Racial Trauma Questionnaire (BBRTQ), a 60-item instrument designed to assess racialised distress within UK-specific institutional and historical frameworks. Forty-five Black British adults (aged 18–55) completed the BBRTQ online. Items were rated on a 5-point Likert scale, developed through qualitative interviews and expert review. Grounded in Helms’ racial identity theory, DeGruy’s post-traumatic slave syndrome, and Fricker’s epistemic injustice framework, exploratory factor analysis revealed a six-factor structure: Emotional Impact, Identity Conflict, Intergenerational Transmission, Systemic Exclusion, Resilience, and Survival Stress. These accounted for 71.2% of variance, with subscale reliability ranging from α = .84 to .91. Scoring yields a Total Trauma Index (TTI) and a Resilience Score, interpreted independently to distinguish trauma burden from culturally grounded coping. Their negative correlation (r = –.42, p < .001) supports the BBRTQ’s non-pathologising design. The BBRTQ demonstrates strong cultural specificity and psychometric robustness, supporting trauma-informed care and systemic reform in UK mental health services
The Black British Racial Trauma Questionnaire (BBRTQ) is a culturally grounded psychometric tool designed to assess racial trauma among Black people in the UK. Developed in response to the limitations of Eurocentric diagnostic frameworks and US-centric racial stress measures, the BBRTQ captures the unique psychological, relational, and systemic dimensions of racialised harm in British contexts. It integrates trauma theory, critical race psychology, and UK-specific histories—including the Windrush scandal, institutional betrayal, and racialised austerity policies—to ensure ecological validity and cultural relevance. The BBRTQ comprises six domains: Emotional Impact of Racialised Experiences, Identity Conflict and Cultural Disconnection, Intergenerational Transmission of Racial Trauma, Systemic Exclusion and Institutional Mistrust, Survival Stress and Adaptive Coping Patterns, and Resilience, Resistance, and Healing Practices. Each domain contains ten items rated on a five-point Likert scale, allowing for nuanced responses across affective, behavioural, and relational dimensions. The scoring architecture separates trauma burden from resilience capacity, producing two distinct sub-scores: the Total Trauma Index (TTI) and the Resilience Score. This dual-scoring system supports ethical, non-pathologising assessment and enables clinicians to identify complex trauma profiles. The BBRTQ is undergoing rigorous psychometric validation, including cognitive interviewing, expert panel review, exploratory and confirmatory factor analysis, reliability testing, and measurement invariance across age, gender, and regional subgroups. Its applications span clinical assessment, therapeutic formulation, supervision, and policy evaluation. It offers practitioners a structured method for exploring racialised distress and tailoring interventions to individual trauma configurations. The tool also supports outcome monitoring and longitudinal tracking of trauma symptoms and healing trajectories. Ultimately, the BBRTQ sets a new standard for culturally valid trauma assessment in the UK. It affirms Black British lived experience, promotes diagnostic visibility, and equips professionals with a robust framework for addressing racial trauma in therapeutic, educational, and institutional settings.
Keywords: Race; racial trauma; African-Caribbeam; Black British